ABSTRACT TOPOGRAPHY: THE POLITICAL LANDSCAPE OF NIEUW HOLLAND IN FRANS VINETES POST FOR THE MAP MURAL BRASILIA QUA PART PARET BELGIS, 1643-1647 - Daniel de Souza Leão Vieira (Clio: Revista de Pesquisa Histórica, 2011)
This text is an investigation on the political landscape of Dutch Brazil and analyses Frans Post‟s vignettes in relation to cartographical space within Georg Marcgraf‟s wall map. After we have compared chorographical effect as it happens on both Post‟s vignettes and drawings (1645), we concluded that they diverge in spite of the fact they share the same subject: a cultural construction of Nieuw Holland‟s Landscape. While the drawings are topographical, related to representations of the fatherly body politic; the vignettes are the stereotyped scenery of overseas foreign land. The former connote the Orangist ideology while the latter refers to the mercantile and civil republicanism within political culture of Seventeenth-Century United Provinces of the Netherlands